Strategi Manajemen Sumber Daya untuk Meningkatkan Kualitas Pengembangan Kurikulum Pendidikan Islam di Madrasah Tsanawiyah Al-Azhar Samarinda - Miki Sandi; Randa Randa; Angga Setiawan; Suratman Suratman; Akhmad Ramli (Al-Munawwarah : Jurnal Pendidikan Islam, 2026)
This study aims to analyze resource management strategies in improving the quality of Islamic education curriculum development at MTs Al-Azhar Samarinda. The study employed a qualitative approach with a field research design. Data collection techniques were carried out through observation, interviews, and documentation. The research informants consisted of the head of the madrasah, the vice principal for curriculum affairs, Islamic Religious Education teachers, and general subject teachers. Data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing, while data validity was tested using source and technique triangulation. The results of the study indicate that resource management strategies in the development of the Islamic education curriculum are implemented through participatory curriculum planning, implementation, and evaluation by involving teachers in the decision-making process. The head of the madrasah applies participatory leadership that supports collaboration among teachers and improves the quality of learning. Curriculum development is also carried out through the integration of Islamic values into learning activities and school culture, such as Qur’an recitation (tadarus), congregational dhuha prayer, and the habituation of Islamic character values. However, curriculum development still faces several challenges, including the suboptimal use of learning technology, limited teacher competence in using digital media, and the high administrative workload in teaching activities. Therefore, it is necessary to enhance teacher training and competency development so that the quality of Islamic education curriculum development can be implemented more effectively and innovatively.